Nilai-Nilai Edukatif Menurut Al-Qur’an Surat Al-‘Alaq 1-5 (Kajian Ilmu Pendidikan Islam) - Sulaiman, Husnan; Musthofa, Fikri Ashidiqi (MASAGI : Jurnal Pendidikan Agama Islam, 2023)
Abstract According to Hamka, education is a means to shape the character of the human person who has been born into the world so that he becomes a useful person in his society, so that he knows what is good and what is bad. Apart from that, education must also be based on the belief that above human power there is another supreme power, namely God. Therefore, education must return to educational and religious values. Brain intelligence does not guarantee safety if religious spiritual values ​​are not made the basis. Referring to the problems that occur in the world of education, there are not a few graduates and students who do not master the sciences as they should. This study aims to find educational values ​​according to Al-Qur'an Surah Al-'Alaq 1-5 and to find edicative values ​​of Al-Qur'an Surah Al-'Alaq verses 1-5 According to the study of Islamic Education This study uses a library research approach, collecting data by conducting a review study of books, literature, notes, and reports that are related to the research problem. Then proceed with the analysis techniques. This research concludes that: First, the educational values ​​contained in Al-Qur'an Surah Al-'Alaq 1-5 are 1) the value of liking to read, 2) the value of monotheism, 3) the value of science, 4) the value of liking writing or orders to produce scientific work, 5) moral values, 6) worship values ​​and piety values. Second, the educational values ​​in Surah Al-'Alaq verses 1-5 are reading and writing. 2) The value of monotheism, 3) the method of refraction from education, 4) educational media and technology. Qalam in this verse is not limited to the meaning of writing instruments but various equipment related to media and educational technology such as computers, internet, video compact discs, LCDs, projectors, laptops, TVs, newspapers, and so on.